A premium sanction board applicable to customs infractions - La Noire Núñez, José Antonio (2021)
A customs regime of infractions and sanctions are created in any state law based on a set of obligations. In other words, the board of sanctions applicable to the expected infractions in the customs general law cannot be seen on an isolated manner. On the other hand, we must go back to the General Customs Law, approved by Legislative Decree No. 1053 and amendments, to analyze the new regulatory framework that, since 2018, has incorporat- ed important modifications, especially section two, differencing operators from their customs obligations in three large groups: Foreign Trade Opera- tors, Intervening Operators and lastly, Third Parties. Furthermore, refer us to the Sanction Board and how the level of compliance of customs operations are measured through the administrative infractions commission with its respective sanctions that go, depending on the severity, from pecuniary fines, confiscation of merchandise, to suspension, cancellation or disqualification to exercise functions; and in between, Customs Administration with the imperius need to make flexible and digitize its processes in pandemic times and economic economic reactivation.